Triffin Dilemma and International Monetary System : Evidence from Pooled Mean Group Estimation - Guan, Long Fei; Lau, Wee Yeap (Korea Distribution Science Association (KODISA), 2018)
This study is motivated based on concern from some renowned scholars and central bankers whom have raised the issue of the sustainability of the International Monetary System (IMS). Using the panel data set of four major international currencies, USD, JPY, EUR and GBP from 1973 to 2013 with Pooled Mean Group (PMG) estimator, to re-examine whether Triffin dilemma still exists through investigating the relationship between the reserve share, current account balance and real effective exchange rate. The evidence from the result indicates that Triffin dilemma exists only in the long run, and shows that in the long-run, current account balance is proportionate to the increased real effective exchange rate while varies inversely with the reserve shares. However, the estimation for the short-run is not significant to prove the existence of Triffin dilemma. In addition, we investigated the non-dollar panel sample and found that the international monetary system still suffers from Triffin dilemma even without the dollar. To overcome Triffin dilemma, immediate step such as having currency swap mechanism is recommended. In medium term, a multi-polar Monetary System is suggested, and in the longer time, a supranational currency will be used to replace all the currencies in the world.